Integrated sustainable landscape management through deforestation-free jurisdiction project in Lam Dong and Dak Nong, Vietnam - Reymondin, Louis; Vantalon, Thibaud; Luong, Phuong Thi (2024)
Terra-i operation and use for near real-time forest monitoring in Lac Duong, Di Linh district (Lam Dong province) and Dak Glong, Dak R’lap district (Dak Nong province)